2020
DOI: 10.3928/01913913-20200622-01
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on Binocular Vision Normative Values

Abstract: Purpose: To establish a relationship between age and horizontal heterophoria, horizontal fusional vergence amplitudes, and vergence facility testing. Methods: The sample consisted of 112 patients with a mean age of 39.8 ± 14.97 years (range: 18 to 65 years) and was composed of 61 women (54.5%) and 51 men (45.5%). The non-presbyopic group included patients 18 to 39 years old (n = 49) and the presbyopic group included patients 41 to 65 years old (n = 63).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…This concurs with Zhou and collegues 28 in China. However, it is in contrast with studies conducted in Spain, 29 which found signi cant associations between fusion vergence and age. Again the nding of this study may be attributed to differences in study population as the current review enrolled young participants only.…”
Section: This Paper Provides An Overview Of Bv Functions Including Ac...contrasting
confidence: 87%
“…This concurs with Zhou and collegues 28 in China. However, it is in contrast with studies conducted in Spain, 29 which found signi cant associations between fusion vergence and age. Again the nding of this study may be attributed to differences in study population as the current review enrolled young participants only.…”
Section: This Paper Provides An Overview Of Bv Functions Including Ac...contrasting
confidence: 87%
“…These results could be explained because exophoria increases and near positive horizontal fusional vergences decrease depending on the age. Thus, the changes in the normal values should be considered for each age range (Sánchez‐González et al, 2020). Moreover, Lai, Hsu, Tung (Lai, Hsu, & Tung, 2020) demonstrated an association between heterophoria and myopia too.…”
Section: Discussionmentioning
confidence: 99%
“…After the age of 70 there is often a decrease in stereo acuity, which is also attributed to a reduction in neurons in the striate cortex in the visual cortex of the brain [20,21,30,82]. It is difficult to separate stereo acuity from visual acuity completely as it is significantly affected and reduced if each eye does not see well enough, stressing the importance of correcting refractive errors in order to achieve maximum stereo acuity [83,84]. Most research was conducted under binocular conditions so it is important to consider the possibility that the results were affected by monocular blur [20,21,30,82].…”
Section: Binocular Visionmentioning
confidence: 99%